Synthesis and Splice-Redirecting Activity of Branched, Arginine-Rich Peptide Dendrimer Conjugates of Peptide Nucleic Acid Oligonucleotides - Saleh, Amer F. (American Chemical Society, 2010)
Arginine-rich cell-penetrating peptides have found excellent utility in cell and in vivo models for enhancement of delivery of attached charge-neutral PNA or PMO oligonucleotides. We report the synthesis of dendrimeric peptides containing 2- or 4-branched arms each having one or more R-Ahx-R motifs and their disulfide conjugation to a PNA705 splice-redirecting oligonucleotide. Conjugates were assayed in a HeLa pLuc705 cell assay for luciferase up-regulation and splicing redirection. Whereas 8-Arg branched peptide−PNA conjugates showed poor activity compared to a linear (R-Ahx-R)(4)−PNA conjugate, 2-branched and some 4-branched 12 and 16 Arg peptide−PNA conjugates showed activity similar to that of the corresponding linear peptide−PNA conjugates. Many of the 12- and 16-Arg conjugates retained significant activity in the presence of serum. Evidence showed that biological activity in HeLa pLuc705 cells of the PNA conjugates of branched and linear (R-Ahx-R) peptides is associated with an energy-dependent uptake pathway, predominantly clathrin-dependent, but also with some caveolae dependence.